(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: The European Glaucoma Society recommends that selective laser trabeculoplasty (SLT) be considered as a first-line treatment option for patients with mild or moderate primary open-angle glaucoma (POAG) or for those who have not responded well to medications. Purpose: To assess the efficacy of POAG treatment with SLT based on examination of the function of Schlemm’s canal (SC) Methods: This paper presents the results of clinical studies and one-month dynamic follow-up of 38 POAG patients (52 eyes) who underwent SLT with a Tango Reflex YAG/SLT laser (Ellex, USA) at the VISUS clinic (Zaporizhzia). Of the 38 patients, 18 (47.37%) were males and 20 (52.63%) females. Patient age ranged from 58 to 85 years (mean age ± standard deviation, 69 ± 9.9 years). Results: There was a significant difference in the response to SLT between eyes with a functional blockage and those with an organic blockage of SC. In the former eyes, true intraocular pressure (P0) decreased from 25.66 ± 0.41 mmHg before SLT to 19.2 ± 0.24 mmHg, outflow facility coefficient increased by 40%, and Becker’s coefficient decreased by 46.63% at 1 month after SLT (p < 0.05). In eyes with an organic blockage of SC, P0 changed from 27.69 ± 0.51 mmHg before SLT to 27.64 ± 0.49 mmHg at 1 week, and even increased to 28.75 ± 0.52 mmHg at month 1 after SLT (p ˃ 0.05), and tonography characteristics did not change. Conclusion: The current study demonstrated that the success rate of SLT in eyes with POAG was 69.2%. The success rate, however, may reach 100% (with a mean percentage IOP reduction of 25.18%, 40 percent increase in the outflow facility coefficient, and 46.63 percent decrease in the Becker’s coefficient) if SLT is performed only in POAG eyes with a functional blockage of SC. If established, the functional state of SC may be used for determining indications and contraindications for SLT in POAG.